THE TEACHING OF VOCABULARY - Norqulova, Sarvinoz (Журнал иностранных языков и лингвистики, 2021)
Annotation: The learning of vocabulary is an important part in foreign language learning. The meanings of new words are very frequently emphasized, whether in books or in verbal communication. Vocabulary is a basic of one learns a foreign language.